Reporter-Based Isolation of Developmental Myogenic Progenitors - Kheir, Eyemen; Cusella, Gabriella; Messina, Graziella; Cossu, Giulio; Biressi, Stefano (Frontiers in Physiology, 2018)
The formation and activity of mammalian tissues entail finely regulated processes, involving the concerted organization and interaction of multiple cell types. In recent years the prospective isolation of distinct progenitor and stem cell populations has become a powerful tool in the hands of developmental biologists and has rendered the investigation of their intrinsic properties possible. In this protocol, we describe how to purify progenitors with different lineage history and degree of differentiation from embryonic and fetal skeletal muscle by fluorescence-activated cell sorting (FACS). The approach takes advantage of a panel of murine strains expressing fluorescent reporter genes specifically in the myogenic progenitors. We provide a detailed description of the dissection procedures and of the enzymatic dissociation required to maximize the yield of mononucleated cells for subsequent FACS-based purification. The procedure takes 6-7 hours to complete and allows for the isolation and the subsequent molecular and phenotypic characterization of developmental myogenic progenitors.